Modulação comportamental : música, estresse e cognição - Santos, Amanda Corrêa dos (2023)
Music has been explored as a form of alternative treatment to improve quality of life, cognitive functions, stress, anxiety, and sleep induction. Some stressors, aggravated in the pandemic period of COVID-19, such as noise pollution, social isolation, depression, exposure to long working hours, evoke poor sleep quality. Psychological disorders, abuse of sleep-inducing drugs, poor diet, high stress levels, are examples of problems caused by lack of sleep. For this, studies prove the benefit and impact of the use of music on the cognitive skills of animals, such as rodents. The zebrafish (Danio rerio) has been widely used in research due to its genetic homology with humans. In the present study, by means of a literature review, we consolidate the use of musical stimuli as a way to improve pain symptoms, anxiety, stress, and sleep quality; promoting physical and psychological benefits to the individuals. Furthermore, we experimentally proved that sessions of Solfeggio frequency 963Hz reverses cognitive damage and stress level induced by 24-hour light exposure in zebrafish, corroborating with studies that demonstrate benefits in humans. The experiment was conducted using intermittent (2 hours or 6 hours twice a day) or continuous (24 hours) sessions to Solfeggio frequency music (963Hz) in adult zebrafish subjected to circadian rhythm alteration (24-hour light exposure). While 24-hour light exposure evokes cognitive deficits and elevates cortisol levels, these effects were reversed by exposure to the music sessions. These findings suggest a positive modulation of cognitive and endocrine responses in adult zebrafish to music and reinforce the zebrafish as a robust and sensitive model organism for neurocognitive and neuroendocrine research.